Analisis Kalimat Tanya pada Acara Mata Najwa Episode "Hukuman Suka-suka" sebagai Alternatif Bahan Pembelajaran Menulis Kalimat Tanya bagi Siswa Kelas IV Sekolah Dasar - Saphira, Chika Aulia; Wardana, Deni; Widjojoko, Widjojoko (Didaktika, 2021)
Writing an interrogative sentence is very important for elementary school students. In addition to being used in preparation for conducting interviews, interrogative sentences are also used in everyday life. So far, students only know how the interrogative sentence is, without paying attention to what things must be considered in making the interrogative sentence. Through the learning material to write question sentences, it is certainly hoped that it will help students prepare themselves for interview activities. Many interview activities are found on television programs, one of the programs that features interview activities, namely the Mata Najwa program. This study aims to determine how the form of interrogative sentences used by Najwa Shihab in the Mata Najwa episode "like-like punishment" and then can be used as learning materials for writing interrogative sentences for fourth grade elementary school students. The method used is content analysis method. The data collection technique in this study used document analysis techniques. The subject or source of data in this study is primary data sourced from Mata Najwa's shows accessed via YouTube. The results of this study were found as many as 109 interrogative sentences raised by Najwa Shihab which were then classified according to the interrogative sentences which used the interrogative word and the interrogative sentence which did not use the interrogative word. In this study, there are 63 interrogative sentences that use interrogative words which are placed at the beginning, middle, and end of the sentence. The use of interrogative sentences that do not use the interrogative word in this study is as many as 46 sentences which are marked by the sound of the rising intonation at the end of the pronunciation. From the research that has been done, it is obtained learning materials to write question sentences for fourth grade elementary school students.